2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20788
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Global Virtual Teams to Traditional Study Abroad Programs in Engineering Education

Abstract: He is also concurrently a M.B.A. candidate at the Marriott School of Management at Brigham Young University. He graduated summa cum laude with a B.S. mechanical engineering degree from Brigham Young University, Idaho. Ball has previously worked in the automotive and aerospace industries. His current research is focused on identifying and validating global competencies for engineers and developing and evaluating educational programs designed to enable engineering students to develop global competence. He is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…He also recommended that higher education engineering programs prepare engineering students for a global environment by developing professional skills, fostering international internships, teaching an appreciation for other cultures, implementing international collaborations, and promoting foreign language skills. Ball et al (2012) also conducted a study of industry and academic experts to further explore the most important global competencies needed in engineering disciplines. The top industry rated competencies were 'appreciate and respect cultural differences', 'collaborate and work on a multicultural team', 'use collaboration technologies in intercultural interactions', 'practice tolerance and flexibility', and 'practice cultural equality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He also recommended that higher education engineering programs prepare engineering students for a global environment by developing professional skills, fostering international internships, teaching an appreciation for other cultures, implementing international collaborations, and promoting foreign language skills. Ball et al (2012) also conducted a study of industry and academic experts to further explore the most important global competencies needed in engineering disciplines. The top industry rated competencies were 'appreciate and respect cultural differences', 'collaborate and work on a multicultural team', 'use collaboration technologies in intercultural interactions', 'practice tolerance and flexibility', and 'practice cultural equality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research on global virtual team projects has suggested that these experiences can contribute to engineering students' development of intercultural skills. For example, one study compared students who had studied abroad with those who participated in a course with global virtual teams, finding that although the study abroad students saw higher gains in intercultural competence, there were some areas where the students in the course scored just as high or better (Ball et al, 2012;Zaugg et al, 2013). Other studies have identified similar outcomes from global virtual team projects, including understanding cultural differences (Miranda et al, 2017), awareness of diversity (Reid & Garson, 2017), and intercultural maturity (Alves, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few studies of these earlier studies have explored students' experiences while they are participating in global virtual teams to understand how opportunities for both learning and conflict may arise in this environment. Prior studies have used surveys, questionnaires, interviews, and reflections to understand the development of competencies in students but without much emphasis on student perspectives (Alves, 2018;Ball et al, 2012;Duus & Cooray, 2014;Liu et al, 2015;Miranda et al, 2017;Whitman et al, 2005). In contrast, our study aimed to uncover student perceptions of their experiences in global virtual teams in a holistic manner by analyzing student reflections at the start and end of the semester.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collaborative global teaming projects are less costly for the college as well as for students compared to sending students and faculty overseas. In addition, more students can be accommodated through this method than through many of the other program types 19 . However, very little is documented on virtual global team-based learning challenges and effectiveness in furthering education of engineering students.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the program, students may or may not have the opportunity to meet face to face with their peers at other participating universities. Examples of this type of program include Partners for the Advancement of Collaborative Engineering (PACE) sponsored projects 19 .…”
Section: Introductionmentioning
confidence: 99%